2017
DOI: 10.1371/journal.pone.0181709
|View full text |Cite
|
Sign up to set email alerts
|

Experience with a second language affects the use of fundamental frequency in speech segmentation

Abstract: This study investigates whether listeners’ experience with a second language learned later in life affects their use of fundamental frequency (F0) as a cue to word boundaries in the segmentation of an artificial language (AL), particularly when the cues to word boundaries conflict between the first language (L1) and second language (L2). F0 signals phrase-final (and thus word-final) boundaries in French but word-initial boundaries in English. Participants were functionally monolingual French listeners, functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 26 publications
4
15
0
Order By: Relevance
“…One straightforward explanation of these results is that the learning of intonational cues may be more difficult if it requires listeners to suppress an L1-based relationship between a cue and a word edge than if it requires them to learn a new, L2-based relationship between a cue and a word edge. Functionally monolingual English listeners have been shown to use F0 rise as a cue to word-initial boundaries but not as a cue to word-final boundaries (e.g., Tremblay, Namjoshi, Spinelli, Broersma, Cho, Kim, Martínez-García & Connell, 2017; Tyler & Cutler, 2009). For English listeners, therefore, suppressing the association between an H tone and word-initial boundaries is more difficult to accomplish than learning a new association between an H tone and the last syllable of a phrase-final word.…”
Section: Discussionmentioning
confidence: 99%
“…One straightforward explanation of these results is that the learning of intonational cues may be more difficult if it requires listeners to suppress an L1-based relationship between a cue and a word edge than if it requires them to learn a new, L2-based relationship between a cue and a word edge. Functionally monolingual English listeners have been shown to use F0 rise as a cue to word-initial boundaries but not as a cue to word-final boundaries (e.g., Tremblay, Namjoshi, Spinelli, Broersma, Cho, Kim, Martínez-García & Connell, 2017; Tyler & Cutler, 2009). For English listeners, therefore, suppressing the association between an H tone and word-initial boundaries is more difficult to accomplish than learning a new association between an H tone and the last syllable of a phrase-final word.…”
Section: Discussionmentioning
confidence: 99%
“…boundary in the native and unfamiliar languages, segmentation of the unfamiliar language is enhanced, whereas if a given cue signals different word boundaries in the two languages, segmentation of the unfamiliar language is inhibited (e.g., Kim et al, 2012;Tremblay et al, 2017;Tyler & Cutler, 2009). What is unclear from this research, however, is how the fine-grained phonetic realization of a given cue to word boundary impacts speech segmentation in cases where the cue signals the same word boundary in the native and unfamiliar languages but does so differently in the two languages.…”
mentioning
confidence: 99%
“…For example, Tremblay et al (2012) found that as the French-L2 proficiency of English-L1 learners increased, so did their reliance on phrase-final lengthening to locate word boundaries in French. Furthermore, Tremblay et al (2017) showed that English native speakers who have reached a high proficiency level in L2-French used F0 as a word offset cue in an artificial language learning paradigm, while monolingual English speakers did not. In turn, French native speakers who have reached a high proficiency level in L2-English relied less on F0 as a word offset cue than did monolingual French speakers (Tremblay et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Tremblay et al (2017) showed that English native speakers who have reached a high proficiency level in L2-French used F0 as a word offset cue in an artificial language learning paradigm, while monolingual English speakers did not. In turn, French native speakers who have reached a high proficiency level in L2-English relied less on F0 as a word offset cue than did monolingual French speakers (Tremblay et al, 2017). These results prompted the authors to suggest that "listeners' use of prosodic cues to word boundaries is, at least to some degree, adaptive (i.e., it is modulated by both L1 and L2 experience), and it is not selective (i.e., segmentation strategies cannot be selected as a function of how useful they are for segmenting the unfamiliar language)" (Tremblay et al, 2017, p. 14).…”
Section: Introductionmentioning
confidence: 99%